2020
DOI: 10.3389/fpls.2020.00691
|View full text |Cite
|
Sign up to set email alerts
|

WRKY Transcription Factor OsWRKY29 Represses Seed Dormancy in Rice by Weakening Abscisic Acid Response

Abstract: For efficient plant reproduction, seed dormancy delays seed germination until the environment is suitable for the next generation growth and development. The phytohormone abscisic acid (ABA) plays important role in the induction and maintenance of seed dormancy. Previous studies have identified that WRKY transcription factors can regulate ABA signaling pathway. Here, we identified an Oswrky29 mutant with enhanced dormancy in a screen of T-DNA insertion population. OsWRKY29 is a member of WRKY transcription fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 59 publications
0
34
0
1
Order By: Relevance
“…Other species‐specific genes were annotated as cytochrome P450 (27), cysteine/histidine‐rich C1 (32), domain of unknown function (DUF) (76), glycoside hydrolase (22), NAC domains (14), peptidases (40), protein kinases (15), WRKY (15), and zinc finger proteins (35). Many of these putatively function in development and defense (Hwang et al ., 2014; Singh et al ., 2014; Xu et al ., 2015; Dong et al ., 2019) or might be related to seed germination and dormancy (Papi et al ., 2000; Christianson et al ., 2009; Joseph et al ., 2014; Santamaria et al ., 2014; Raineri et al ., 2016; Zhou et al ., 2020), as expected as many seed samples (234 of 294) were included for RNA‐seq data used in this annotation. Since Ae.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Other species‐specific genes were annotated as cytochrome P450 (27), cysteine/histidine‐rich C1 (32), domain of unknown function (DUF) (76), glycoside hydrolase (22), NAC domains (14), peptidases (40), protein kinases (15), WRKY (15), and zinc finger proteins (35). Many of these putatively function in development and defense (Hwang et al ., 2014; Singh et al ., 2014; Xu et al ., 2015; Dong et al ., 2019) or might be related to seed germination and dormancy (Papi et al ., 2000; Christianson et al ., 2009; Joseph et al ., 2014; Santamaria et al ., 2014; Raineri et al ., 2016; Zhou et al ., 2020), as expected as many seed samples (234 of 294) were included for RNA‐seq data used in this annotation. Since Ae.…”
Section: Resultsmentioning
confidence: 76%
“…arabicum v3.1 annotation, 77 WRKY TFs were found, six more than in the other Brassicaceae on average (71.25). These TFs have been reported to participate in seed germination (Raineri et al ., 2016 ; Zhou et al ., 2020 ). Since part of the WRKY complement was detected as species‐specific by OrthoFinder, it might represent a lineage‐specific expansion of these TFs.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have indicated the crucial regulatory roles of WRKY transcription factors in plant growth and development, physiological and biochemistry processes, biotic and abiotic stress response [ 13 , 14 , 15 , 16 ]. For instance, overexpression of the transcription factor TaWRKY2 enhances drought stress tolerance and increase grain yield in transgenic wheat ( Triticum aestivum L.) [ 17 ]; while overexpression of OsWRKY29 represses seed dormancy by directly downregulating the expression of OsABF1 and OsVP1 in rice ( Oryza sativa L.) [ 18 ]. What is noteworthy is that the regulatory functions of WRKY genes are closely associated with multiple plant hormone-mediated signal pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The roles of several WRKY genes in plant growth and developmental processes, such as seed dormancy, germination, leaf senescence, and plant height, were also identified in previous studies. For example, in rice, the Oswrky29 mutant displayed enhanced seed dormancy [ 25 ]. In Arabidopsis , a lack of WRKY41 reduced primary seed dormancy [ 26 ].…”
Section: Introductionmentioning
confidence: 99%